Melancholics on the Vistula River - Piechota, Dariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article discusses the theme of melancholy in Polish prose of the 21st century, using four contemporary novels – „Pokolenie Ikea” [The IKEA generation] (2012) by Piotr C., „Wszyscy jesteśmy hipsterami” [We are all hipsters] (2016) by Dariusz Radecki, „Melanżeria” [Melangery] (2011) by Anna Klara Majewska and „Za pięć rewolta” [Five minutes to a revolt] (2011) by Dawid Kain – as conspicuous examples of its presence. The author suggests that due to the increased pace of social and technological changes the generation of thirty-year-olds experiences a feeling of melancholy, formerly characteristic for elderly people and analyses the protagonists of the novels selected to present how they cope with a reality that does not fulfil them.
Translated by Elżbieta Rokosz.
Keywords: melancholy; youth; consumption; transience; depression